炎症性皮膚状態を処置するためのミノサイクリン (2021)
本出願は、低減された用量のミノサイクリンを含む医薬組成物を、炎症性皮膚状態を処置することを必要とする対象に投与することによって炎症性皮膚状態を処置する方法であって、前記投与が、炎症性皮膚状態を処置するためのミノサイクリンの有効な血漿または間質液濃度をもたらす、方法に関する。本出願は、低減された用量のミノサイクリンを含む医薬組成物を投与して、炎症性皮膚状態のための有効な処置を提供することによって、酒さなどの前記炎症性皮膚状態を処置する方法を提供する。 The present application relates to a method of treating an inflammatory skin condition by administering a pharmaceutical composition comprising a reduced dose of minocycline to a subject in need thereof, wherein said administration provides an effective plasma or interstitial fluid concentration of minocycline for treating the inflammatory skin condition.